Phylogenetic Classification and Functional Review of Autotransporters - Clarke, Kaitlin R.; Hor, Lilian; Pilapitiya, Akila; Luirink, Joen; Paxman, Jason J.; Heras, Begoña (Frontiers in Immunology, 2022)
Autotransporters are the core component of a molecular nano-machine that delivers cargo proteins across the outer membrane of Gram-negative bacteria. Part of the type V secretion system, this large family of proteins play a central role in controlling bacterial interactions with their environment by promoting adhesion to surfaces, biofilm formation, host colonization and invasion as well as cytotoxicity and immunomodulation. As such, autotransporters are key facilitators of fitness and pathogenesis and enable co-operation or competition with other bacteria. Recent years have witnessed a dramatic increase in the number of autotransporter sequences reported and a steady rise in functional studies, which further link these proteins to multiple virulence phenotypes. In this review we provide an overview of our current knowledge on classical autotransporter proteins, the archetype of this protein superfamily. We also carry out a phylogenetic analysis of their functional domains and present a new classification system for this exquisitely diverse group of bacterial proteins. The sixteen phylogenetic divisions identified establish sensible relationships between well characterized autotransporters and inform structural and functional predictions of uncharacterized proteins, which may guide future research aimed at addressing multiple unanswered aspects in this group of therapeutically important bacterial factors.